Визначення впливу окислювального та абсорбційного об'ємів на процес абсорбції NOₓ в технології нітратної кислоти - Пугановський, Олег Валентинович; Подустов, Михайло Олексійович; Дзевочко, Олександр Михайлович; Шутинський, Олексій Григорович; Печенко, Тамара Іванівна (НТУ "ХПІ", 2017)
Проведен анализ влияния окислительного и абсорбционного объемов на процесс абсорбции оксидов азота в технологии азотной кислоты. Показано, что для интенсификации абсорбции оксидов азота необходимо изменять окислительный и абсорбционный объемы по высоте абсорбционной колонны.

The influence of the oxidation and absorption volumes for the absorption process of nitrogen oxides in the technology of nitric acid. It is shown that in order to intensify the absorption of nitrogen oxides is necessary to change the oxidation and absorption volumes for the absorpti on column height.
To determine the influence of oxidation and absorption volumes for the absorption process of NOₓ in the technology of nitric acid
Keywords: нітратна кислота; абсорбція; окислювальний об'єм; абсорбційний об'єм